2018
DOI: 10.2174/1573396314666180221163924
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dyslipidemia and Other Cardiovascular Risk Factors in Youth with Diabetes

Abstract: CVD risk factors are common in children with diabetes mellitus. Good glycemic control, early identification, and effective life-long management of all CVD risk factors may help decrease the high rate of premature morbidity and mortality in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Insulin resistance is known to be associated with an adverse cardiometabolic risk factor profile, and both obesity and insulin resistance appear to contribute independently to CV risk in representative populations of youth . In our obese dysglycemic adult and youth cohorts, the dominant associations with CV risk factors were from insulin sensitivity without a separate effect of obesity.…”
Section: Discussionmentioning
confidence: 70%
“…Insulin resistance is known to be associated with an adverse cardiometabolic risk factor profile, and both obesity and insulin resistance appear to contribute independently to CV risk in representative populations of youth . In our obese dysglycemic adult and youth cohorts, the dominant associations with CV risk factors were from insulin sensitivity without a separate effect of obesity.…”
Section: Discussionmentioning
confidence: 70%
“…Dyslipidemia is a common disease that can lead to atherosclerosis and increase the risk of coronary heart disease and ischemic stroke [4]. Studies have shown that the incidence of abnormal lipid metabolism is increasing each year, and lipid metabolism disorder can increase the risk of cardiovascular disease and the incidence of related diseases [5]. Current studies have shown that there is a dose-response relationship between urinary metal levels and coronary heart disease [6,7].…”
mentioning
confidence: 99%